Material for decomposing cooking pollutants as well as preparation method and application thereof
By using catalytic materials of conductive and adsorption layers on cooking utensils, using the characteristics of power-on and high oil absorption, the problems of high labor intensity, high energy consumption and food safety of cooking pollutant treatment in the prior art are solved, and low-voltage power-on is achieved Deep oxidation and efficient pollutant decomposition under dirt.
Patent Information
- Application Number
- CN202310786936.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-06-30
AI Technical Summary
The prior art has high labor intensity, high energy consumption, and poor cleaning effect when dealing with cooking pollutants. The self-cleaning method has food safety problems and high costs, making it difficult to adapt to the treatment of high air volume and low concentration pollutants.
Using a catalytic layer material including a conductive layer and an adsorption layer, the conductive layer generates an electric heating effect to decompose pollutants into water and carbon dioxide through energization. The adsorption layer captures and transfers oil and oil fume through high oil absorption and hydrophobicity, reducing the resistance to diffusion and mass transfer. Catalytic oxidation reaction.
It realizes deep oxidation and removal of dirt under low voltage power-on, the decomposition products are non-toxic and harmless, and have low energy consumption. It is suitable for large smoke flow and low contact time scenarios, improving cleaning efficiency and food safety.
Smart Images

Figure BDA0004312540130000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cooking pollutant treatment, and in particular to a material for decomposing cooking pollutants, a preparation method and application thereof. Background Art
[0002] Grease, sugar, soy sauce, etc. are indispensable condiments for cooking delicious dishes, but the cooking process easily forms pollutants such as oil smoke / grease, VOCs, and soup, and even mixes in some flour, meat and other food residues, making it difficult to clean kitchen utensils. The existing solution is mainly to clean with detergents, but this method has the problem of high labor intensity; there are also some easy-to-clean methods, that is, by adjusting the surface energy of the coating, reducing the adhesion of dirt on the coating surface, or improving the hydrophilic and / or oleophobic ability of the coating surface, thereby reducing the cleaning labor intensity, but this method has high requirements for the material of cooking utensils.
[0003] There are also those that use self-cleaning technology. The main self-cleaning methods include high-temperature carbonization, catalytic combustion, high-temperature steam treatment and other methods. The so-called decomposition technology is often combined with high-energy ion composite catalytic technologies such as photocatalysis and plasma ozone. The structure is complex. For example, for range hoods, this technology is difficult to adapt to large air volume and low-concentration pollutant treatment.
[0004] There is even a "self-cleaning" technology that mainly relies on adsorption. When dirt is generated, it will be adsorbed into the microscopic pores of the coating, but it will not be removed. When the pores are saturated with adsorption, the "self-cleaning" function is lost, and the adsorbed dirt is prone to breed bacteria, etc., posing a major food safety problem.
[0005] The current self-cleaning methods have high energy consumption, and there are problems such as unsatisfactory cleaning effect and service life. For example, catalytic combustion mostly uses precious metal catalytic materials, which are expensive and difficult to promote. The use of non-precious metal catalytic materials has unsatisfactory catalytic effect at low temperatures. Summary of the invention
[0006] The first technical problem to be solved by the present invention is to provide a material for decomposing cooking pollutants with good decomposition effect in view of the current status of the prior art.
[0007] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned material for decomposing cooking pollutants in view of the current status of the prior art.
[0008] The third technical problem to be solved by the present invention is to provide an application of the above-mentioned material for decomposing cooking pollutants in view of the current status of the prior art.
[0009] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a material for decomposing cooking pollutants, characterized in that it includes a substrate and a catalytic layer arranged on the substrate, the catalytic layer includes a conductive layer, and the conductive layer includes a conductive catalyst that can generate an electrothermal effect after power is applied, thereby decomposing cooking pollutants into water and carbon dioxide.
[0010] In order to make the conductive catalyst have a good conductive effect, the conductivity of the conductive catalyst is 10 -1 -10 3 S / m, the catalytic decomposition of cooking pollutants is more thorough.
[0011] Preferably, the conductive catalyst is at least one of tin oxide, antimony oxide, tungsten oxide, zinc oxide, titanium oxide, and rare earth oxides. These conductive catalysts are conductive materials that can be commercially adopted on a large scale, are easy to promote industrialization, and are reasonably priced.
[0012] Preferably, the conductive layer further comprises a film-forming material, and the film-forming material is at least one of silicon oxide, aluminum oxide, and boron oxide. The film-forming material provides a basic network skeleton structure for the conductive layer, so that the conductive catalyst is fully filled therein, plays a role in fixing and forming a film for the conductive catalyst, and at the same time has a regulating effect on the thermal expansion coefficient of the conductive layer, so that the conductive catalyst has good adhesion and strength on the surface of the insulating layer or the surface of the conductive layer. If there is no film-forming material, the conductive catalyst cannot adhere to the surface of the insulating layer and cannot function.
[0013] Preferably, the catalytic layer further comprises an adsorption layer, the adsorption layer comprises an adsorption material and a film-forming material, the film-forming material in the adsorption layer is at least one of silicon oxide, aluminum oxide, and boron oxide, the adsorption material has oil absorption and hydrophobicity, and the specific surface area of the adsorption material is 10m 2 / g-200m 2 / g, the oil absorption is (5-150)g / 100g, and the contact angle of water is >90°. The synergistic effect of the conductive layer and the adsorption layer can better decompose grease, because diffusion mass transfer is an important step in the catalytic reaction, and even becomes a rate-controlling step in some catalytic reactions. Due to the excellent lipophilic properties of the adsorption layer, pollutants such as grease and oil fume are quickly adsorbed and captured when they reach the surface of the adsorption layer, reducing the escape of pollutants and improving the decomposition efficiency; more importantly, after pollutants such as grease and oil fume are captured, due to the excellent lipophilic properties of the adsorption layer, the pollutants have a very small contact angle with the adsorption layer, which can better wet the adsorption layer, that is, the pollutants can be effectively spread on the surface of the adsorption layer and the conductive layer, rather than accumulating in a local area, so that the conductive layer can effectively contact with the pollutants, reducing the diffusion mass transfer resistance, which is conducive to the occurrence of catalytic oxidation reactions.
[0014] The present invention selects an adsorption material with a high oil absorption capacity and performs hydrophobic modification so that the prepared adsorption layer has the adsorption capacity for oily pollutants, that is, hydrophobicity and lipophilicity. The water generated by the reaction can be discharged in time, and the water vapor in cooking does not stay on the surface of the coating. The oil smoke / grease, VOCs and organic condiments cooking dirt can be effectively captured and enriched by the coating and transferred to the catalytic interface, which is conducive to the occurrence of dirt decomposition reactions; in addition, water / water vapor is kept away from the coating, which can inhibit the corrosion of water-soluble salts, acids, alkalis and other species to the coating, which is beneficial to the stability of the coating, and can prevent electrical problems such as short circuits caused by water / water vapor and its salts, acids, alkalis and other electrolytes. The material of the present application can be used in scenarios including but not limited to range hoods with large smoke flow, low contact time, and low concentration of pollutants.
[0015] The thickness of the catalytic layer is preferably between 50 μm and 300 μm, more preferably between 100 μm and 200 μm.
[0016] Preferably, the adsorption material is at least one of titanium oxide, aluminum oxide and silicon oxide.
[0017] Preferably, the substrate is made of metal, which has a higher use value. It can also be made of ceramic, etc., but not plastic. In addition, because the substrate is made of metal, an insulating layer is provided between the substrate and the catalytic layer.
[0018] Preferably, the insulating layer is at least one of silicon oxide, aluminum oxide, and boron oxide. The thickness of the insulating layer is 10 μm-300 μm, and 10 μm-200 μm enamel is preferred for food-grade applications, and 10 μm-50 μm ceramic film and other inorganic non-metallic materials are preferred for non-food-grade applications.
[0019] The technical solution adopted by the present invention to solve the second technical problem is: a method for preparing the material for decomposing cooking pollutants, characterized in that it comprises the following steps:
[0020] (1) coating an insulating layer on the surface of a substrate to form a semi-finished product 1, and sequentially drying and calcining the semi-finished product 1 at a drying temperature between 100° C. and 200° C. and a calcining temperature between 200° C. and 850° C. to form a semi-finished product 2;
[0021] (2) After the catalytic layer is coated on the insulating layer on the semi-finished product 2, the product is dried and calcined in sequence, with the drying temperature being between 100°C and 200°C and the calcining temperature being between 200°C and 850°C, to produce a finished product.
[0022] The catalytic layer is coated on the insulating layer on the semi-finished product two, and one scheme is: in the step (2), the conductive layer is first coated on the insulating layer on the semi-finished product two, and then the adsorption layer is coated on the conductive layer.
[0023] The catalytic layer is coated on the insulating layer on the semi-finished product two. Another solution is: in the step (2), the conductive layer and the adsorption layer are first mixed to form a composite slurry, and then the composite slurry is coated on the insulating layer on the semi-finished product two.
[0024] Preferably, the preparation method of the conductive layer is as follows: a film-forming material is mixed with water to form a slurry, and a dispersion of a conductive catalyst is evenly mixed with the slurry to form the conductive layer, and the mass percentage of the film-forming material and the conductive catalyst is between 99:1 and 50:50.
[0025] Preferably, the preparation method of the conductive catalyst dispersion is as follows: disperse the conductive catalyst in water and stir to mix evenly. This method is quick and simple to operate.
[0026] Preferably, the method for preparing the conductive catalyst dispersion comprises the following steps:
[0027] (1) purchasing a powdered conductive catalyst, dispersing the powdered conductive catalyst in water to form a dispersion, and adjusting the pH of the dispersion to 8-14 with a pH adjuster;
[0028] (2) mixing tetraethyl orthosilicate and silicone oil to form a mixed solution 1, wherein the mass ratio of tetraethyl orthosilicate to silicone oil is between 60:40 and 90:10;
[0029] (3) adding the mixed solution 1 in step (2) to the dispersion in step (1) under stirring at room temperature, wherein the mass ratio of the mixed solution 1 to the dispersion is 1:99-49:51, and continuing to stir evenly after the addition is completed to form a mixed solution 2;
[0030] (4) Adding a pH adjuster to the mixed solution 2 of step (3) to adjust the pH of the mixed solution 2 to 7, thereby obtaining a dispersion of the conductive catalyst.
[0031] The dispersion of the conductive catalyst prepared in this way has a core-shell structure, in which the core layer is a composite particle formed by a low surface energy species and the shell layer is a conductive catalyst. During the heat treatment of the catalytic layer, due to the low surface energy characteristics of the core-shell structure, it will migrate and enrich to the surface of the catalytic layer, thereby forming a continuous three-dimensional conductive catalytic network on the surface of the catalytic layer. In addition, the core-layer structure reduces the use of conductive catalytic materials while ensuring the catalytic and conductive effects, thereby reducing the overall cost.
[0032] Because the present application relates to a composite coating composed of a substrate, an insulating layer, a conductive layer, an adsorption layer, etc., the thermal expansion coefficient matching between the coatings becomes the key. Once the thermal adaptation, the composite coating will peel off and other problems will occur, thereby losing structural strength and catalytic decomposition performance. The present application combines the basic principle of topological optimization design method, and extends and optimizes the material structure. Specifically, when designing the core-shell structure, a variety of materials with higher and lower thermal expansion coefficients are selected, and a bottom-up method is adopted when the core-shell structure is prepared, and the core layer material and the shell layer material are chemically bonded at the interface by a hydroxyl condensation reaction, thereby improving the bonding strength of the core-shell material. Therefore, the composite material formed by the above scheme can obtain a core-shell composite material with different thermal expansion coefficients by regulating the type and content of the core-shell material. More importantly, in the present application, the core layer structure is a high expansion coefficient material, and the shell layer structure is a low expansion coefficient material with a conductive catalytic function. When the core layer material has a large thermal expansion coefficient, the core-shell particles are close to the shell conductive catalytic material, thereby maintaining a better conductive catalytic performance.
[0033] In the above scheme, the preparation method of the adsorption layer includes the following steps: mixing the film-forming material with water to form slurry two, and evenly mixing the adsorption material with slurry two to form the adsorption layer, and the mass percentage of the adsorption material to the film-forming material is between 99:1 and 50:50.
[0034] The technical solution adopted by the present invention to solve the third technical problem is: an application of the above-mentioned material for decomposing cooking pollutants, characterized in that the material is applied to a cooking utensil, the substrate is arranged on the cooking utensil, or the substrate is a local part of the cooking utensil. The substrate is a component made of common household appliance processed metal materials such as stainless steel, enameled steel, galvanized sheet, etc. The component can be installed on the cooking utensil, or the component is a local part of a structural member such as an oven back panel, an inner tank, a stove energy collecting cover, a fire cover, a range hood filter, a flue, etc.
[0035] In the above scheme, the cooking utensil is a steamer or an oven or a steam-bake all-in-one machine or a stove or a range hood.
[0036] Compared with the prior art, the advantages of the present invention are as follows: 1. After the material of the present invention is energized, the catalytic layer can work to achieve the deep oxidation and removal function of dirt, and can achieve deep decomposition of oil smoke / grease, VOCs and organic condiments cooking dirt, and the decomposition products are non-toxic and harmless components such as carbon dioxide and water, which can be directly discharged into the kitchen without harming the environment and human body.
[0037] 2. The catalytic layer of the present invention includes a conductive layer, which accepts electrons from the external circuit under low-voltage power supply, can reduce the activation energy of lattice oxygen and quickly form highly oxidatively active particles, thereby achieving complete decomposition of dirt in a relatively short time at a safe voltage below 36V and cooking temperature, without the need to increase the voltage or decomposition temperature, and the decomposition process is safe and energy-saving. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with specific embodiments.
[0039] Embodiment 1:
[0040] The material for decomposing cooking pollutants in this embodiment includes a substrate, an insulating layer and a catalytic layer arranged on the surface of the insulating layer, the catalytic layer includes a conductive layer and an adsorption layer, the conductive layer includes a film-forming material and a conductive catalyst that can generate an electrothermal effect after power is supplied to decompose cooking pollutants into water and carbon dioxide, and the adsorption layer includes an adsorption material and a film-forming material.
[0041] The preparation method of the material of this application is as follows:
[0042] (1) Pre-treating the substrate by sandblasting, degreasing or washing;
[0043] Then, the insulating layer is coated on the surface of the substrate to form a semi-finished product 1, and the semi-finished product 1 is dried and calcined in sequence, with a drying temperature of 200° C. and a drying time of 10 min, and a calcination temperature of 850° C. and a calcination time of 10 min to form a semi-finished product 2, wherein the insulating layer is the purchased enamel material;
[0044] (2) First, a conductive layer is coated on the insulating layer on the semi-finished product 2, and then the adsorption layer is coated on the conductive layer, and then drying and calcining are performed in sequence. The drying temperature is 200°C, the drying time is 10 minutes, the calcination temperature is 850°C, and the calcination time is 10 minutes, so that the finished product is made.
[0045] The preparation method of the conductive layer is as follows:
[0046] (a) The purchased conductive catalyst (LaCoO3) was dispersed in water, the conductivity of the conductive catalyst was 0.621 S / m, the particle size of the conductive catalyst was 25 nm, and the mass ratio of the conductive catalyst to water was 1:1. The mixture was stirred at a stirring speed of 4000 rpm for 15 min to make the conductive catalyst evenly dispersed in the water to prepare a dispersion of the conductive catalyst.
[0047] (b) The film-forming material (enamel powder) is stirred evenly in water to form a supporting slurry 1, wherein the mass ratio of the film-forming material to water is 1:1. The dispersion of the conductive catalyst obtained in step (a) is added to the aforementioned slurry 1 and stirred to mix evenly. The stirring speed is 5000 rpm and the stirring time is 60 min. Thus, the conductive layer is formed. The mass ratio of the conductive catalyst to the film-forming material is 99:1 and the thickness of the conductive layer is 100 μm.
[0048] The preparation method of the adsorption layer comprises the following steps: mixing a film-forming material (enamel powder) with water to form a slurry; and mixing an adsorption material (titanium dioxide, with a specific surface area of 200 m 2 / g, oil absorption 150g / 100g) was stirred and mixed evenly with slurry 2 to form the adsorption layer, the stirring speed was 5000rpm, the stirring time was 60min, and the mass percentage of the adsorption material to the film-forming material was 85:15.
[0049] Example 2
[0050] This embodiment differs from Embodiment 1 in the following ways:
[0051] 1. The conductive catalyst of this embodiment uses ATO (antimony-doped tin oxide, the antimony doping amount is 10%), and the conductivity is 6.33×10 1 S / m, particle size 5 μm;
[0052] 2. In steps (1) and (2) of the material preparation method, the drying and calcination conditions are as follows: drying temperature is 140°C, drying time is 20 min, calcination temperature is 600°C, and calcination time is 3 min;
[0053] 3. In step (b) of the method for preparing the conductive layer: the mass ratio of the conductive catalyst to the film-forming material is 50:50, and the thickness of the conductive layer is 170 μm;
[0054] 4. In the method for preparing the adsorption layer: the mass percentage of the adsorption material to the film-forming material is 99:1;
[0055] 5. The adsorption material is silicon dioxide, with a specific surface area of 50m 2 / g, oil absorption 30g / 100g.
[0056] For other details, please refer to Example 1.
[0057] Example 3
[0058] The preparation method of the conductive catalyst dispersion of Example 3 is different from that of Example 1, and the conductive catalytic material is different, that is, step (a) of the preparation method of the conductive layer is different from that of Example 1. The rest can refer to Example 1. The thickness of the conductive layer in this example is 200 μm.
[0059] In this embodiment, the method for preparing the dispersion of the conductive catalyst comprises the following steps:
[0060] (1) Purchase powdered conductive catalyst (LaSrCoO3) with a conductivity of 1.32×10 3 S / m, the conductive catalyst particle size is 1 μm, and then dispersed in water to form a dispersion, and the pH of the dispersion is adjusted to 12 with a pH adjuster (urea);
[0061] (2) mixing tetraethyl orthosilicate and silicone oil to form a mixed solution 1, wherein the weight average molecular weight of the silicone oil is 5000, and the mass ratio of tetraethyl orthosilicate to silicone oil is 75:25;
[0062] (3) adding the mixed solution 1 in step (2) to the dispersion in step (1) under stirring at room temperature, wherein the mass percentage of the mixed solution 1 to the dispersion is 49:51, and after the addition is completed, stirring is continued at 4000 rpm for 15 min to form a uniform mixed solution 2;
[0063] (4) Adding a pH adjuster (formic acid) to the mixed solution 2 of step (3) to adjust the pH of the mixed solution 2 to 7, thereby obtaining a dispersion of the conductive catalyst.
[0064] Example 4
[0065] The difference between this embodiment and embodiment 3 is that:
[0066] 1. In the preparation method of the dispersion of the conductive catalyst: the mass ratio of tetraethyl orthosilicate to silicone oil is 90:10; the mass percentage of the mixed solution 1 to the dispersion is 1:99; the thickness of the conductive layer is 200 μm, and the pH of the dispersion is adjusted to 8 using a pH adjuster (urea) in step (1);
[0067] 2. In steps (1) and (2) of the material preparation method, the drying and calcination conditions are as follows: drying temperature is 100°C, drying time is 20 min, calcination temperature is 200°C, and calcination time is 10 min;
[0068] 3. In step (b) of the method for preparing the conductive layer: the mass ratio of the conductive catalyst to the film-forming material is 90:10;
[0069] 4. In the preparation method of the adsorption layer: the mass percentage of the adsorption material and the film-forming material is 50:50, and the adsorption material is alumina with a specific surface area of 10m 2 / g, oil absorption 5g / 100g.
[0070] Example 5
[0071] The difference between Example 5 and Example 3 is that:
[0072] 1. Step (2) of the method for preparing the material of the present application is different from that of Example 3.
[0073] In this embodiment, in step (2), the conductive layer and the adsorption layer are first mixed to form a composite slurry, and then the composite slurry is coated on the insulating layer on the semi-finished product second, and then dried and calcined.
[0074] 2. In the method for preparing a dispersion of a conductive catalyst: in step (1), the pH of the dispersion is adjusted to 14 using a pH adjuster (urea).
[0075] For other details, please refer to Example 3.
[0076] Example 6
[0077] The difference between this embodiment and embodiment 3 is that:
[0078] 1. In the preparation method of the conductive catalyst dispersion: the mass ratio of ethyl orthosilicate to silicone oil is 60:40, the mass percentage of the mixed solution 1 to the conductive catalyst dispersion is 35:65; the thickness of the conductive layer is 100 μm;
[0079] 2. In steps (1) and (2) of the material preparation method, the drying and calcination conditions are as follows: drying temperature is 100°C, drying time is 20 min, calcination temperature is 200°C, and calcination time is 10 min;
[0080] 3. In step (b) of the method for preparing the conductive layer: the mass ratio of the conductive catalyst to the film-forming material is 99:1.
[0081] For other details, please refer to Example 3.
[0082] Example 7
[0083] The difference between Example 7 and Example 3 is that this example does not have an adsorption layer, and the conductive layer is directly coated on the insulating layer. For other details, please refer to Example 3.
[0084] Comparative Example 1
[0085] The difference between Comparative Example 1 and Example 3 is that this example does not have a conductive layer, that is, the adsorption layer is directly coated on the insulating layer. For other details, please refer to Example 3. The material made in Comparative Example 1 is not conductive, and only the thermal catalytic performance is evaluated.
[0086] Comparative Example 2
[0087] The difference between Comparative Example 2 and Example 3 is that this example does not have a catalytic layer, and the rest can refer to Example 3, that is, there is only a substrate and an insulating layer coated on the substrate. The material made in Comparative Example 2 is not conductive, and only the thermal catalytic performance is evaluated.
[0088] The test results of the above embodiments and comparative examples are as follows:
[0089]
[0090] In the above table " √ " indicates that the material has this coating, " × ” means the material does not have this coating.
[0091] The above test method is as follows:
[0092] a. Electric assisted catalysis: The coating sample is a 350×350mm sample, which is placed in a 72L reactor. 3g of edible oil is sprayed on the sample, and the reaction is energized for 30 minutes. After the reaction, the gas phase components are detected by gas chromatography and the mineralization rate is calculated; the gas phase temperature in the reactor when the mineralization rate is 50% is recorded as T50. The power-on voltage is a constant voltage of 12V.
[0093] b. Thermal catalysis: Compared with a, the heating reaction is used instead of the power-on reaction, and the rest is the same as a. The heating temperature for the mineralization rate test is 500℃, and the T50 test is based on the actual temperature rise.
[0094] The material for decomposing cooking pollutants prepared in the present application can be electrified using existing technology, generally by setting electrical components on the cooking utensil, the electrical components including a positive electrode, a negative electrode, a circuit board, wires, etc. electrically connected to the material.
Claims
1. A material for decomposing cooking pollutants, characterized in that The invention comprises a substrate and a catalytic layer arranged on the substrate. The catalytic layer comprises a conductive layer. The conductive layer comprises a conductive catalyst which can generate an electrothermal effect after being energized, thereby decomposing cooking pollutants into water and carbon dioxide.
2. The material according to claim 1, characterized in that: The conductivity of the conductive catalyst is 10 -1 -10 3 Between S / m.
3. The material according to claim 2, characterized in that: The conductive catalyst is at least one of tin oxide, antimony oxide, tungsten oxide, zinc oxide, titanium oxide, and rare earth oxide.
4. The material according to any one of claims 1 to 3, characterized in that: The conductive layer further includes a film-forming material, and the film-forming material is at least one of silicon oxide, aluminum oxide, and boron oxide.
5. The material according to claim 4, characterized in that: The catalytic layer also includes an adsorption layer, which includes an adsorption material and a film-forming material. The film-forming material in the adsorption layer is at least one of silicon oxide, aluminum oxide, and boron oxide. The adsorption material has oil absorption and hydrophobicity.
6. The material according to claim 5, characterized in that: The adsorption material is at least one of titanium oxide, aluminum oxide and silicon oxide.
7. The material according to claim 5, characterized in that: The substrate is made of metal, and an insulating layer is provided between the substrate and the catalytic layer.
8. The material according to claim 7, characterized in that: The insulating layer is at least one of silicon oxide, aluminum oxide and boron oxide.
9. A method for preparing the material for decomposing cooking pollutants according to claim 7, characterized in that: The steps include: (1) coating an insulating layer on the surface of a substrate to form a semi-finished product 1, and sequentially drying and calcining the semi-finished product 1 at a drying temperature between 100° C. and 200° C. and a calcining temperature between 200° C. and 850° C. to form a semi-finished product 2; (2) After the catalytic layer is coated on the insulating layer on the semi-finished product 2, the product is dried and calcined in sequence, with the drying temperature being between 100°C and 200°C and the calcining temperature being between 200°C and 850°C, to produce a finished product.
10. The preparation method according to claim 9, characterized in that: In the step (2), the conductive layer is first coated on the insulating layer on the semi-finished product 2, and then the adsorption layer is coated on the conductive layer.
11. The preparation method according to claim 9, characterized in that: In the step (2), the conductive layer and the adsorption layer are first mixed to form a composite slurry, and then the composite slurry is coated on the insulating layer on the second semi-finished product.
12. The preparation method according to claim 9, characterized in that: The preparation method of the conductive layer is as follows: a film-forming material is mixed with water to form a slurry, and a dispersion of a conductive catalyst is evenly mixed with the slurry to form the conductive layer. The mass percentage of the film-forming material and the conductive catalyst is between 99:1 and 50:
50.
13. The preparation method according to claim 12, characterized in that: The preparation method of the conductive catalyst dispersion is as follows: disperse the conductive catalyst in water and stir to mix evenly.
14. The preparation method according to claim 12, characterized in that: The method for preparing the conductive catalyst dispersion comprises the following steps: (1) dispersing a powdered conductive catalyst in water to form a dispersion, and adjusting the pH of the dispersion to 8-14 with a pH adjuster; (2) mixing tetraethyl orthosilicate and silicone oil to form a mixed solution 1, wherein the mass ratio of tetraethyl orthosilicate to silicone oil is between 60:40 and 90:10; (3) adding the mixed solution 1 in step (2) to the dispersion in step (1) under stirring at room temperature, wherein the mass ratio of the mixed solution 1 to the dispersion is 1:99-49:51, and continuing to stir evenly after the addition is completed to form a mixed solution 2; (4) Adding a pH adjuster to the mixed solution 2 of step (3) to adjust the pH of the mixed solution 2 to 7, thereby obtaining a dispersion of the conductive catalyst.
15. The preparation method according to claim 9, characterized in that: The preparation method of the adsorption layer comprises the following steps: mixing a film-forming material with water to form a second slurry, and uniformly mixing the adsorption material with the second slurry to form the adsorption layer, wherein the mass percentage of the adsorption material to the film-forming material is between 99:1 and 50:
50.
16. Use of the material for decomposing cooking pollutants according to any one of claims 1 to 15, characterized in that: The material is applied to a cooking utensil, the substrate is arranged on the cooking utensil, or the substrate is a local part of the cooking utensil.
17. The use according to claim 16, characterized in that: The cooking utensil is a steamer or an oven or a steam-bake all-in-one machine or a stove or a range hood.
Citation Information
Patent Citations
Catalyst and preparation method of coated catalyst
CN109821564A
Cooking utensil and preparation method thereof
CN113509054A
Decomposition catalyst
JP2002224567A
Cooker
JP2007107851A
Cooking machine with ceramic coating and febricationmethod thereof
KR1020050114554A
